Post Traumatic Stress Disorder (PTSD) On a Sample Of The Wives Of The Martyrs -Field Study In Area OF Jablah - - Sbeirah, Fouad; Sady, Rima; Badr, Eman (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research aimed to know the differences in the degree of PTSD depending on the variables; period of the shock , Educational level and The nature of the housing. In This research it is used Davidson's scale of PTSD ,which is based in the diagnosis DSM-IV which was translated to Arabic by Abdul Aziz Thabet (2006). The research is applied in Jableh. The sample consisted of (50) Wives. The research is found the following results: there is no statistically significant differences in the degree of PTSD depending on the variables,( period of shock and Educational level) , as too there are statistically significant differences in the degree of PTSD depending on the variable The nature of the housing.